The Effects of Captions on EFL Learners' Comprehension of English-Language Television Programs. (20th July 2016) - Rodgers, Michael; Webb, Stuart
Abstract : The Multimedia Principle (Fletcher & Tobias, 2005) states that people learn better and comprehend more when words and pictures are presented together. The potential for English language learners to increase their comprehension of video through the use of captions, which graphically display the same language as the spoken dialogue, has been documented in previous research. However, studies have generally used short videos (Markham & Peter, 2003; Montero Perez, Peters & Desmet, 2014) or videos designed for language learning (Chung, 1999) rather than episodes of L2 television programs that students are most likely to watch on their own outside of the classroom. The present study aimed to fill this gap by investigating the comprehension of 372 Japanese university students who watched ten 42-minute episodes of an American television program with and without captions. While viewing the episodes, the participants completed comprehension tests. Analysis indicated that although the participants who viewed the episodes with captions had comprehension scores that were slightly higher across all episodes, their scores were only significantly different for three of the ten episodes. The results revealed that captions are likely to aid comprehension when episodes are most difficult. Explanations for the findings and pedagogical applications are offered.